SERUM PROGESTERONE AND OESTRADIOL PROFILE IN PSEUDOPREGNANT AND PREGNANT GOATS BELOW 3 MONTHS POSTSERVICE - K. Devalal (Journal of Veterinary and Animal Sciences, 2019)
The study was conducted with an objective to compare the serum progesterone and oestradiol levels of early pseudopregnant (Group I) goats before and after treatment (with double regime of PGF2α) with cycling animals (Group II) at similar reproductive stages. No significant difference in serum progesterone levels was observed between group I and II under study, whereas progesterone levels of non-pregnant does were significantly lower than pregnant does on day 21 post-service. There existed a highly significant difference in oestradiol concentrations between the groups. It can be concluded from the present study that, oestradiol can be considered as a tool to differentiate pseudopregnancy from pregnancy